Խաչատուր Իսկանդարյանի ստեղծագործական կյանքի ուրվագիծը - Նարե Նադարյան (ՀՀ ԳԱԱ հրատ.)
Данная статья представляет жизнь народного художника РА Хачатура Искандаряна. Скульптор за время своей многолетней творческой жизни принял участие в большом числе выставок и конкурсов, удостаивался множества призов и наград. This article depicts the creative life of the National painter and sculpture of Armenia, Khachatur Iskandaryan. During his long creative life he participated in many exhibitions, competitions and was awarded a number of rewards.
Keywords: Biography; Sculpture; Painting